KARAKTERISTIK TEGANGAN TEMBUS AC PADA MATERIAL ISOLASI PADAT CAMPURAN EPOXY RESIN DENGAN TONGKOL JAGUNG - Arfan Saputra Arfan Saputra; Lanto Mohammad Kamil Amali (Foristek, 2022)
Abstrak – The development of insulation in electric power systems meets the optimal level of reliability. This phenomenon is a challenge in finding new materials to isolate electricity use. One of the insulating materials being developed is an epoxy resin polymer material. This study aims to describe the characteristics of epoxy resin composites added with corncob ash filler as a high-voltage insulation material. The cob ash filler, which is known to contain silica resistant to high temperatures, has good inhibition and can increase mechanical strength. This study was conducted using a direct experimental method in which the isolation of epoxy resin was mixed with corncob ash filler with a mixed variation of 0.5 g, 1 g, 1.5 g, and 2 g. The results show that the more corncob ash filler in the epoxy resin, the faster the failure to penetrate the insulating material made. The breakdown voltage value is 21.64kV on pure epoxy resin insulation material, 10.28kV on a mixture of 0.5 gram corncob ash filler and epoxy resin, 8.93kV on a mixture of 1 gram corncob ash filler and epoxy resin, 7,81kV on a mixture of 1,5 grams corncob ash filler and epoxy resin, and 7,26kV on a mixture of 2 gram corncob ash filler and epoxy resin.